Heat Effect Induces Production of Inflammatory Cytokines Through Heat Shock Protein 90 Pathway in Cornea Cells. (April 2013) - Tsai, Ming-Ju; Hsu, Ya-Ling; Wu, Kwou-Yeung; Yang, Rei-Cheng; Chen, Yi-Jen; Yu, Hsin-Su; Kuo, Po-Lin
Abstract Purpose: Many studies have been conducted to elucidate the molecular consequences of ultraviolet irradiation, whereas little is known about the effect of infrared radiation on ocular disease. Heat is generated as a consequence of infrared irradiation, in addition to photons, and heat shock is widely considered to be an environmental stressor. Our previous study has demonstrated that heat shock (42 °C) induces apoptosis of Statens Seruminstitut Rabbit Cornea (SIRC) cells. However, the biological effect of mild heat shock (39 °C), which does not induce apoptosis, on SIRC cells has not been studied yet. Methods: The SIRC cells were treated with mild heat shock and the expression of inflammatory cytokines, including interleukin-1β (IL-1β) and interleukin-6 (IL-6), in the mRNA and protein levels were then assayed with reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assay, respectively. The levels of heat shock protein 90 (HSP90), phosphorylated AKT, phosphorylated IκBα and nuclear NF-κB were assessed with immunoblot assays; the involvement of these molecules in the signaling pathway were further assessed by using specific inhibitor for HSP90, AKT or NF-κB. Results: Mild heat shock increased the production of inflammatory cytokines, IL-1β and IL-6. Mild heat shock increased expression of HSP90, which increased the phosphorylation of AKT. The activated AKT then increased the phosphorylation of IκBα, resulting in nuclear translocation of NF-κB, which up-regulated the expression of IL-1β and IL-6 in SIRC cells. Conclusions: These findings suggest a critical role for the HSP90-AKT-NF-κB signaling pathway in mild heat shock-induced inflammatory response of cornea cells.